Peningkatan Brand Awareness UMKM Cookies Melalui Strategi Social Media Marketing - Antara, I Made Yuda Yudi; Wardani, Kadek Devi Kalfika Anggria Anggria (Universitas Mercu Buana, 2025)
Roemah Cookies, an MSME in Denpasar, currently has not fully utilized digital marketing even though it offers various variants of cookies through WhatsApp orders. In the digitalization era, conventional marketing has become less effective, and brand awareness has become a key factor in market competition. This activity was carried out using the Participatory Action Research (PAR) method and aims to increase brand awareness of MSME cookies through Instagram social media marketing. This service has succeeded in having a positive impact in increasing brand awareness and implementing social media marketing for UMKM Roemah Cookies. Through the stages of planning, coordination and information obtained online, the next steps have been prepared. The material presented at the implementation stage has provided an understanding of the importance of social media marketing as well as practical steps in implementing it. The evaluation shows an increase in followers and positive interactions with followers on Instagram, illustrating success in building active interactions with consumers. Thus, UMKM Roemah Cookies is able to apply the knowledge acquired and is ready to continue to utilize social media marketing as an effective tool for growing brand awareness and business in the digital era.